2016
DOI: 10.1177/1937586716651967
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Hand Hygiene With a Lighting Prompt

Abstract: The healthcare system frequently relies on expensive technology to improve healthcare delivery, but implementation of low-cost, low-technology methods such as this light may be effective in prompting hand hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…We confirmed this finding. Some publications contained particularly detailed interpretation and commentary [6,8,9,23,25], others comparatively little [7,10,17,19]. [6, 8, 9, 11, 12, 14, 16, 17, 18 19, 20, 24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We confirmed this finding. Some publications contained particularly detailed interpretation and commentary [6,8,9,23,25], others comparatively little [7,10,17,19]. [6, 8, 9, 11, 12, 14, 16, 17, 18 19, 20, 24].…”
Section: Discussionmentioning
confidence: 99%
“…[6, 8, 9, 11, 12, 14, 16, 17, 18 19, 20, 24]. In eight publications it was suggested that observing hand hygiene in the control group might have caused a Hawthorne effect, reducing the difference between control and test group outcomes [9,10,12,15,16,17,19]. In three publications it was suggested that installing extra hand hygiene dispensers in control wards might have the same effect [11,12,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations